2017
DOI: 10.1111/ijcp.12974
|View full text |Cite
|
Sign up to set email alerts
|

Influence of renal function on anticoagulation control in patients with non-valvular atrial fibrillation taking vitamin K antagonists

Abstract: Summary Background and Purpose Chronic kidney disease (CKD) has been related to poor anticoagulation control and an increased risk of bleeding. This study aims to evaluate the association between impaired renal function (eGFR <60 mL/min/1.73 m2) and anticoagulation control in patients with non‐valvular atrial fibrillation (AF) on vitamin K antagonists (VKA) therapy. We also assessed whether the predictive value of the SAMe‐TT2R2 score prevailed for subgroups both with and without CKD. Methods This is an ancill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The study by Szummer et al [17] found that low TTR caused an increased risk of the composite outcome of ischaemic stroke, myocardial infarction, intracranial haemorrhage and mortality; however, the mean TTR was exceptionally high (83%) in this observational study. Other studies have similarly demonstrated that good anticoagulation control was independently associated with lower risk of stroke, mortality, and major bleeding [14, 16, 18]. Nonetheless, Bonde et al [18] found that this effect was only observed in patients with an eGFR between 30 and 60 mL/min/1.73 m 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Szummer et al [17] found that low TTR caused an increased risk of the composite outcome of ischaemic stroke, myocardial infarction, intracranial haemorrhage and mortality; however, the mean TTR was exceptionally high (83%) in this observational study. Other studies have similarly demonstrated that good anticoagulation control was independently associated with lower risk of stroke, mortality, and major bleeding [14, 16, 18]. Nonetheless, Bonde et al [18] found that this effect was only observed in patients with an eGFR between 30 and 60 mL/min/1.73 m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have shown that even moderate CKD was associated with lower TTR [15, 16]. In addition, traditional predictive factors of reduced TTR were not useful in patients with CKD [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROC curves are widely used in the performance evaluation of medical diagnostic tests, which can obtain multiple pairs of true positive rates (TPR) and false positive rates (FPR) by changing the diagnostic boundary. The curve is drawn with FPR as the abscissa, and with TPR as the ordinate (19,20). The diagnostic value of the diagnostic test is reflected by calculating and comparing the AUC.…”
Section: Discussionmentioning
confidence: 99%
“…Lobos‐Bejarano et al () found that the TTR decreased with declining renal function, with only 42% of those with an estimated glomerular filtration rate (eGFR) ≤29 ml/min per 1·73 m 2 meeting the TTR ≥ 65%, with an increase in the variability of INRs. A study of patients in Sweden with AF discharged on warfarin after myocardial infarction (MI) found that warfarin reduced the risk of a composite of death, MI and ischaemic stroke without increasing bleeding risk in those patients with an eGFR < 15 ml/min per 1·73 m 2 (Carrero et al , ).…”
Section: Time In Therapeutic Range and Esrdmentioning
confidence: 99%